What Does Matter?: Idols and Icons in the Nenets Tundra - Laur Vallikivi (Journal of Ethnology and Folkloristics)
This paper examines a mission encounter in the Nenets reindeer herders’ tundra. In post-Soviet Arctic Russia, Pentecostal and Baptist missionaries of Russian and Ukrainian origin have been fighting against idolatry and trying to persuade the Nenets to burn their sacred images or khekhe’’. They claim that among the indigenous Siberians idolatry exists in its quintessential or prototypical form, as it is described in the Bible. I shall suggest that this encounter takes place in a gap, in which the Nenets and Protestant have different understandings of language and materiality. Missionaries rely simultaneously on the ‘modern’ ideology of signification and the ‘non-modern’ magic of the material. They argue that idols, which are ‘nothing’ according to the scriptures, dangerously bind the ‘pagans’’ minds. For reindeer herders, for whom sacred items occupy an important place in the family wellbeing, the main issue is how to sever the link with the spirits without doing any damage.